Determinants of Skilled Birth Attendant Utilization at Chelia District, West Ethiopia - Dufera, Adugna; Bala, Elias Teferi; Desta, Habtamu Oljira; Taye, Kefyalew (International Journal of Reproductive Medicine, 2020)
Background. An estimated 303,000 maternal deaths occurred globally in 2015 from which sub-Saharan Africa alone accounted for 201,000 (66%) of the maternal deaths, and most of these are attributed to complications of pregnancy and childbirth due to the absence of institutional delivery by skilled attendants. Objective. The aim of this study was to assess institutional delivery utilization and associated factors among mothers who gave birth in the last one year in Chelia District. Methodology. A community-based cross-sectional study design supplemented by a qualitative method was employed from March 15 to 30, 2018. A multistage sampling technique was used to select 475 study participants. Quantitative data were collected using structured questionnaires, and focus group discussions were employed to get qualitative data. The data were entered to EpiData version 3.1 and exported to the statistical package version 21 for analysis. Descriptive statistics and bivariate and multivariate logistic regression analysis were computed to measure the strength of association between dependent and independent variables at a p value of <0.05. Results. Among the respondents, 216 (46.2%) utilized institutional delivery service. Monthly income (AOR=4.465, 95%CI=1.729,11.527), antenatal care attendance (AOR=0.077, 95%CI=0.008,0.73), knowledge of mothers about their expected date of delivery (AOR=0.297, 95%CI=0.179,4.93), intended pregnancy (AOR=0.326, 95%CI=0.162,0.654), discussion with health extension workers about the place of delivery at home visit (AOR=0.11, 95%CI=0.023,0.523), knowledge of mothers about the existence of the waiting area in health facilities (AOR=0.14, 95%CI=0.023,0.84), and number of children (AOR=0.119, 95%CI=0.029,0.485) had a significant association with institutional delivery utilization. Conclusion. Utilization of institutional delivery was low and far away from the expected country target in the district. The health sector should strive to increase proportion of institutional delivery by reaching pregnant mothers with timely antenatal care service provision and enhancing family planning provision.